2010
DOI: 10.1002/bmc.1494
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moringa oleifera on pharmacokinetic disposition of rifampicin using HPLC‐PDA method: a pre‐clinical study

Abstract: The influence of active fraction isolated from pods of an indigenous plant, Moringa oleifera (MoAF) was studied on the pharmacokinetic profile of the orally administered frontline anti-tuberculosis drug rifampicin (20 mg/kg b.w.) in Swiss albino mice. The antibiotic rifampicin alone and in combination with MoAF (0.1 mg/kg b.w.) was administered orally and heparanized blood samples were collected from the orbital plexus of mice for plasma separation at 0, 1, 2, 3, 4 and 5 h, post treatment. Plasma rifampicin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A few experimental studies reported that M. oleifera can alter the pharmacokinetic profile of other drugs, such as rifampicin and amodiaquine, indicating that future studies should also focus on the detailed pharmacokinetic and drug interaction profile of M. oleifera.…”
Section: Future Prospectivementioning
confidence: 99%
See 1 more Smart Citation
“…A few experimental studies reported that M. oleifera can alter the pharmacokinetic profile of other drugs, such as rifampicin and amodiaquine, indicating that future studies should also focus on the detailed pharmacokinetic and drug interaction profile of M. oleifera.…”
Section: Future Prospectivementioning
confidence: 99%
“…In addition, the detailed pharmacokinetic profile of M. oleifera and its bioactive constituents, including absorption, distribution, metabolism, and excretion, together with the bioavailability and possible drug interactions should also be studied. A few experimental studies reported that M. oleifera can alter the pharmacokinetic profile of other drugs, such as rifampicin 144 and amodiaquine, 145 indicating that future studies should also focus on the detailed pharmacokinetic and drug interaction profile of M. oleifera.…”
Section: Future Prospectivementioning
confidence: 99%
“…The widespread use of herbal medicinal plants in conjunction with conventional medicines presents further complications and should also be considered in pharmacogenomics research due to herb–drug interactions, which may affect efficacy and toxicity profiles of pharmaceutical drugs [ 12 ]. Herbal medicinal plants such as Moringa oleifera have shown inhibitory effects of cytochrome P450 enzymes and affect bioavailability of some HIV/AIDS and TB drugs [ 13 , 14 ]. Microarray-based mRNA expression profiling has shown the effects of herbal medicines on expression of genes in drug response pathways [ 15 ].…”
Section: Role Of Pharmacogenomics In Sub-saharan Africa (Ssa)mentioning
confidence: 99%
“…This observation was corroborated by a recent preclinical study on the influence of M. oleifera pods on the pharmacokinetic disposition of rifampicin using high-performance liquid chromatography–photodiode array. The active fraction isolated from air dried pods of the plant mixed with rifampicin and administered to the experimental animals enhanced systemic availability of the drug and suppressed the drug metabolizing cytochrome P-450 ( Pal et al, 2010 ). Few reports are available on the antimicrobial activity of M. oleifera pods.…”
Section: Introductionmentioning
confidence: 99%